Foot Strike Pattern Detection Using a Loadsol® Sensor Insole - Keiichiro Hata; Yohei Yamazaki; Misato Ishikawa; Toshio Yanagiya (Sensors, 2025)
Understanding the foot strike pattern (FSP) and impact force of running-related injuries is crucial for athletes and researchers. This study investigated a novel method for detecting FSP using the loadsol® sensor insole during treadmill running. Twelve collegiate athletes ran at three different speeds (12, 15, and 20 km/h), with their FSP determined using both the kinematic method based on the foot strike angle and the loadsol® method based on the plantar force applied to the rear-, mid-, and forefoot sensor areas. This study provides significant insights into FSP detection. Comparing the kinematic method to the loadsol® method, the rearfoot, midfoot, and forefoot strike detection rates were 94.7%, 37.1%, and 81.8%, respectively. Moreover, the FSP was not uniform, even during treadmill running at a constant speed, with most participants exhibiting mixed patterns across different speeds. The loadsol® sensor insole could offer a promising device for in-field measurement of FSP and impact forces, potentially helping researchers and athletes better understand and predict the potential running-related injury risks by monitoring step-to-step variations in running biomechanics.